Transmission Capacity Estimation for the Medium Voltage Level of Smart Grid - Jiri Vodrazka (Advances in Electrical and Electronic Engineering, 2017)
It is clear that communication infrastructure will must be gradually extended to lower levels of energy grid, primary to medium and low-voltage levels. The information capacity of the backhaul part of the communication network will be continuously increased as a result of Smart Grid services expanding. In this paper, the data rate analysis of the backhaul links on medium-voltage power grid level is presented. The network model and calculation of aggregate data rate method for the medium-voltage section is designed. In next part, the experimental results of broadband power line communication are presented and these results are compared with aggregated data transmission requirements. Usability of broadband power line communication is discussed and gradual transition to optic fibre communications is predicted.